Production Management of the “Asu (Prokontra)” Short Documentary Film - Pipit Setyaningsih; Yeni Rosilawati (Rekam : Jurnal Fotografi, Televisi, Animasi, 2022)
This research focuses on the management of “ASU (Prokontra)” documentary film production, which includes three stages: planning, production, and post-production. This documentary raises the issue of dog slaughtering in Yogyakarta. This research utilized a descriptive qualitative method. The data were gathered through in depth-interview with the director and cameraman of the film. Moreover, secondary data on this research were obtained from the animal community website and social media (Instagram) of Jogja’s Animal Friend and news from local and national mass media. The results revealed three findings: (i)  the director of the “ASU (Prokontra)” documentary film researched to obtain information on dog slaughtering in Yogyakarta; (ii) the director of the film employed an observative approach to record events spontaneously and naturally. The flow of the “ASU (Prokontra)” film production emphasizes the informal shooting process without excessive technical tools and does not require prior design; (iii) the director approached the community as the subject well. This approach was applied to build trust to take the right moment.